2020
DOI: 10.21203/rs.3.rs-73657/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Burden and prevalence of risk factors for severe COVID-19 disease in the ageing European population – A SHARE-based analysis

Abstract: Aim: International health authorities suggest that individuals aged 65 years and above and people with underlying comorbidities such as hypertension, chronic lung disease, cardiovascular disease, cancer, diabetes, and obesity are at increased risk of severe Coronavirus Disease 2019 (COVID-19); however, the prevalence of risk factors is unknown in many countries. Therefore, we aim to describe the distribution of these risk factors across Europe. Subject and Methods: Prevalence of risk factors for severe COVID-1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…Although recent evidence suggests that European women overall have slightly more comorbidities than European men [21], men are generally reported to have more life-threatening conditions, such as cardiovascular diseases, whereas women tend to have more non-fatal chronic diseases, such as migraine, musculoskeletal and autoimmune diseases as well as physical limitations [22][23][24][25]. Thus, the higher risk of death from COVID-19 among men may to some extent be explained by the relatively higher prevalence of underlying comorbidities such as cardiovascular disease, hypertension, diabetes and chronic lung disease [10,26,27]. Nevertheless, sex differences in health depend on the selected health dimension and the age group studied, and not all outcomes show differences between sexes or show very little differences [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Although recent evidence suggests that European women overall have slightly more comorbidities than European men [21], men are generally reported to have more life-threatening conditions, such as cardiovascular diseases, whereas women tend to have more non-fatal chronic diseases, such as migraine, musculoskeletal and autoimmune diseases as well as physical limitations [22][23][24][25]. Thus, the higher risk of death from COVID-19 among men may to some extent be explained by the relatively higher prevalence of underlying comorbidities such as cardiovascular disease, hypertension, diabetes and chronic lung disease [10,26,27]. Nevertheless, sex differences in health depend on the selected health dimension and the age group studied, and not all outcomes show differences between sexes or show very little differences [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Patients suffering from chronic respiratory diseases (CRD) such as chronic respiratory failure, asthma, chronic obstructive pulmonary disease (COPD), interstitial lung diseases (ILD), pulmonary hypertension (PH), sarcoidosis or cystic fibrosis (CF), were immediately considered to be at risk of severe forms of COVID-19 (1). Indeed, COVID-19 is responsible for various respiratory symptoms, from cough with dyspnea to acute respiratory distress syndrome (ARDS) in its most severe presentation (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…There is concern that the respiratory complications of COVID-19 could be deleterious in patients with prior CRD. However, clinical experience and published data covering the outbreak period have suggested that there was a surprisingly low proportion of patients with CRD among patients with COVID-19, especially in its most severe forms (1,5,6).…”
Section: Introductionmentioning
confidence: 99%
“…About 20% of COVID-19 patients are hypertensive, but some older COVID-19 populations have high blood pressure (HBP) rates exceeding 50%, consistent with the prevalence of hypertension in persons of advancing age ( Table 1 ) [ 22 , 23 , 24 ]. The status of hypertension as an independent risk factor for morbidity and mortality in COVID-19 is unclear.…”
Section: Hypertension the Immune System And Covid-19mentioning
confidence: 86%